EKOFEMINISME DAN MORAL AGENCY PEREMPUAN: SINTESIS POST-SEKULAR MENANTANG DUALISME MODERNITAS DAN EKSPLOITASI EKOLOGIS - Neneng Athiyatul Faiziyah; Muhtar Solihin; Munir (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2025)
This article aims to deeply analyze the conceptual relationship between Ecofeminism and Women's Moral Agency through a Post-Secular synthesis as a critical response to the dualism of modernity and the ecological crisis. Methodologically, this study utilizes a synthetic-analytical literature review method reinforced by the narrative sociology framework to elaborate on how women's embodiment experiences are converted into moral agency. The main conceptual findings confirm that women's involvement in environmental preservation transcends mere participation, constituting an agency-structure manifestation that rejects the instrumental rationality of modernity. The post-secular perspective serves as a bridge, explaining that women's moral agency is often rooted in a caring ethic strengthened by local spiritual cosmology, rather than purely secular calculation. The scientific contribution of this study lies in asserting that the synthesis of Ecofeminism and Post-Secularism offers a new ontological basis for sustainable ecological ethics, challenging the hegemony of exploitative development.